Implikasi Hukum Undang-Undang Cipta Kerja terhadap Perlindungan Hak Pekerja Pasca Pailit - Ravi Dana, Arsis; Iftitah, Anik; Zainul Ichwan, Muhammad; Taufan Perdana, Mukhammad (Fakultas Hukum, Universitas Islam Balitar, 2024)
The rapid development of the modern economic sector has intensified competition among companies, consequently increasing the risk of insolvency. This study focuses on the amendments to labor law provisions following the enactment of the Omnibus Law and their impact on the protection of workers' rights after a bankruptcy ruling. There is a gap in understanding the effects of these regulatory changes on workers' rights, particularly in the context of termination of employment due to insolvency. The objective of this research is to analyze the impact of these legal changes on the protection of workers' rights. The methodology used is normative legal research with a legislative approach. The findings indicate significant changes in workers' rights regarding termination due to insolvency. The implications of the Omnibus Law reveal diverse impacts on workers' rights, both positive and negative. This study emphasizes the need for a deeper understanding and adjustments to new regulations to protect workers' rights in Indonesia. The results of this research are expected to provide insights and recommendations for policymakers and legal practitioners in addressing the challenges arising from changes in labor regulations.